Conflicts between People and the Florida Black Bear - Elizabeth F. Pienaar (EDIS)
An adult black bear may eat up to the equivalent calorie content of 38 Big Mac sandwiches a day, and can smell food from one to two miles away. Garbage is the main attractant, but bears are also attracted by bee hives, pet food, barbeque grills, fruit trees, and bird (or wildlife) feeders. Conflicts between people and black bears arise when people fail to remove or secure potential food sources. In their search for food, black bears may damage property and threaten, injure, or kill pets and livestock in order to gain access to their feed. This 5-page fact sheet provides tips for preventing human-bear conflicts and tells how to report conflicts if they happen. Written by Elizabeth F. Pienaar and published by the UF Department of Wildlife Ecology and Conservation, September 2014.